2001
DOI: 10.3322/canjclin.51.4.213
|View full text |Cite
|
Sign up to set email alerts
|

Family Support in Advanced Cancer

Abstract: Changes in the health care system have resulted in a shift of cancer care from the in-patient arena to ambulatory and home settings. This shift has likewise translated into increased family involvement in the day-to-day care of the person with cancer. Cancer patients have multifaceted needs, including disease and treatment monitoring, symptom management, medication administration, emotional support, assistance with personal care, and assistance with instrument care. Family caregivers may be ill prepared to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
401
3
26

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(443 citation statements)
references
References 73 publications
13
401
3
26
Order By: Relevance
“…In our study, most patients asked questions actively about their health conditions at diagnosis, and they were strongly inquisitive to information related to surgical procedures and prognosis. It was claimed that, after surgery, patients paid more attention to symptom control and physical comfort (Given et al, 2001). Our study also indicated that postoperative patients presented evident somatic symptoms, especially sleeping difficulty.…”
Section: Discussionsupporting
confidence: 56%
“…In our study, most patients asked questions actively about their health conditions at diagnosis, and they were strongly inquisitive to information related to surgical procedures and prognosis. It was claimed that, after surgery, patients paid more attention to symptom control and physical comfort (Given et al, 2001). Our study also indicated that postoperative patients presented evident somatic symptoms, especially sleeping difficulty.…”
Section: Discussionsupporting
confidence: 56%
“…Social support may not only affect the representation of patients in COCN categories, but may influence the decision to undergo full evaluation of their cancer [28]. Our inability to measure social support across all patients in this analysis constitutes an important limitation of our study [29].…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, it was observed that different factors such as whether the relative was the mother, daughter, or sister of the patient, whether they had graduated from high school or college, whether the patients had stage IV cancer, whether they were a stayat-home mom, whether they had been living with the patient for a prolonged period of time, and whether they had another relative with breast cancer greatly affected the changes in attitudes and behaviors. Cancer patients being followed up and treated at home need help in many areas (Given et al, 2001). The relatives who take part in the management of their treatment carry huge burdens and may face various social and emotional problems (Sjovall et al, 2009;Siminoff et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature shows that studies conducted on the relatives of cancer patients primarily have dealt only with their psychological problems (Given et al, 2001;Couper et al, 2006;Wagner et al, 2006;Baider et al, 2008;Rhee et al, 2008;Sjovall et al, 2009;Siminoff et al, 2010;Rodríguez et al, 2011;Svetina et al, 2012). No study exists for any kind of cancer that examines the changes in attitudes and behaviors of the relatives of cancer victims.…”
Section: Discussionmentioning
confidence: 99%